Fine needle aspiration cytology diagnosis of caesarean scar endometriosis with histopathological correlation: a case report - Kumar, Sandeep P.; Mallya, Varuna; Kishor, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometriosis is defined as the presence of endometrial tissue outside the endometrium or myometrium. It occurs in 8-15% of women of reproductive age group with abdominal wall endometriosis accounting for only 0.5-1% of all pelvic endometriosis. We present a case of a 25 year old lady who presented with a mass in the anterior abdominal wall over a previous caesarean section scar. Endometriosis was diagnosed on Fine Needle Aspiration Cytology (FNAC) based on the findings of monolayered sheets of endometrial cells, few spindle shaped stromal cells and hemosiderin laden macrophages in the background. Histopathological examination confirmed the cytological diagnosis. Endometriosis in scar tissue is a rare disease which might be difficult to diagnose and should always be considered in evaluation of painful abdominal masses in women. Fine needle aspiration cytology is economical, fast and accurate method to make the diagnosis of scar endometriosis and to plan better surgical approach.